Employees’ Use of Professional Talk to Handle Workplace Surveillance - Backman, Christel; Petersson, Jesper (Surveillance & Society, 2025)
Although workplace surveillance is often conceptualized as a simplified dichotomy of control vs. care or resistance vs. compliance, it can be understood as something that employees enact and in which they take an active part. However, surveillance creates a paradox for those who wish to enact professionalism in their work roles. Whereas being transparent and welcoming scrutiny is considered professional, the visibility that comes with surveillance diminishes the discretionary power and autonomy that are at the core of being professional. In addition, new surveillance technologies implemented into work life may introduce new audiences and thereby new scripts for how to enact professionalism. In this article, we examine how employees use professional talk to handle the paradoxes of workplace surveillance. We ask how employees use surveillance to signal their professionalism and how they balance competing scripts on how to perform professionally to different audiences. Our analysis is based on interviews with two distinct occupational groups affected by the introduction of new types of surveillance technologies into their daily work: private security officers, who may wear body-worn cameras, and doctors, whose medical records are now accessible to their patients online. By examining the ways in which these two distinct occupational groups use professional talk to handle the paradoxes of workplace surveillance, we contribute to the growing research on professional talk as a discursive resource. Furthermore, we augment the literature that adopts a dramaturgical approach to workplace surveillance by extending the understanding of professionalism as something that is done by a profession, instead viewing professionalism as something that can be discursively produced by any occupational group. Finally, our study provides an important contribution to surveillance studies as we continue the exploration of the paradoxes of workplace surveillance, moving beyond the understanding of employees’ reaction to workplace surveillance as either compliance or resistance.